Self-rated health status and associated factors in rural workers - Cleodice Alves Martins; Camila Bruneli do Prado; Júlia Rabelo Santos Ferreira; Eliana Zandonade; Olívia Maria de Paula Alves Bezerra; Luciane Bresciani Salaroli (BMC, 2023)
Abstract Background Self-rated health status can be considered a good predictor of morbidity and mortality and has been used due to its easy assessment and applicability. The instrument is efficient for understanding sociodemographic, environmental and clinical conditions that may be related to the self-rated health status. Thus, this study aims to analyze the self-assessment of health status in rural workers and its association with socioeconomic characteristics, lifestyle, clinical condition and work characteristics. Methods This is a cross-sectional study carried out with 787 male and female rural reporting agriculture as their main source of income in the municipality of Santa Maria de Jetibá. A simple and direct question was used "In general, compared to people your age, how do you rate your own state of health?" to see how rural workers rate their current health status. The independent variables analyzed were socioeconomic, clinical, health and work conditions. The magnitude of the associations was evaluated by means of hierarchical logistic regression. Results It was found that 42.1% of rural workers self-rated their health status as regular or poor. Belonging to socioeconomic classes C (OR = 1.937; 95% CI = 1.009-3.720) or D/E (OR = 2.280; 95% CI = 1.178-4.415), being overweight (or having excess weight) (OR = 1.477; 95% CI = 1.086-2.008), multimorbidity (OR = 1.715; 95% CI = 1.201-2.447) and complex multimorbidity (OR = 1.738; 95% CI = 1.097-2.751) were risk factors for worse self-rated health. Conclusion It was concluded that chronic diseases, socioeconomic status and overweight are risk factors for negative self-rated health. The identification of these determinants through self-rated status can support the planning of actions aimed at improving the health of the rural population. Trial registration This study was approved by the Research Ethics Committee of the Health Sciences Center of the Federal University of Espírito Santo (Protocol No. 2091172; CAAE No. 52839116.3.0000.5060). All research participants gave their informed consent.